Aktivitas Anti Jamur Ekstrak Kulit Kayu Laban (Vitex pubescens Vahl) (Antifungal Activity of Laban (Vitex pubescens) Bark Extracts) - Enih Rosamah; Irawan W. Kusuma; Deny Kurniawan (Masyarakat Peneliti Kayu Indonesia, 2010)
The most of antifungi used in preservatives for wood, food, fungicides, dyestuff, etc. come from synthetical substances, that poisoned not only for fungi but also for environment. In recent, antifungi have been taken from plants. Laban (Vitex pubescens Vahl) is one of high quality wood has been used in Kalimantan (Borneo). Isolation of active compounds will provide scientific validation for the use of laban in another purposes. The object of this research was to evaluate the antifungi activity of bark extract of Laban wood. Extractives solubility of laban bark in methanol was 6.03%. Soluble fractions in n-hexane, diethyl ether, and ethyl acetate yielded 0.27%, 0.39%, and 0.47% respectively. Fractions of n- hexane and diethyl ether contained steroid, flavonoid and carbohydrates. While, ethyl acetate fraction contained triterpeoids, flavonoids, and carbohydrates. Thin layer chromatography (TLC) test of laban bark extracts showed the active compounds of aldehide, keton, and flavonoids. The n-hexane-, diethyl ether-, and ethyl acetate extracts showed the significant anti fungal activities by air-borne method. Antifungal activity of o- hexane extract against Candida albicans was detected by a bioautography assay on TLC plate. The results showed that bark of laban possess potential antifungal activity to be developed as natural antifungal substances.